Published Corporate Accounting Data and Stock Prices - Benston, George J. (Journal of Accounting Research, 1967)
Published accounting reports-the balance sheet, income statement, and funds statement-are prepared for the use of investors, creditors, and others with whom the accountant is not in direct contact. It is therefore difficult for him to determine which data they find useful. Consequently, several arguments have arisen as to which data are the best. Examples of these competing theories are the current operating performance concept versus clean surplus, price level versus historical cost depreciation, and sales versus cash flow versus net income. Even if accountants knew which constructs were best, other questions would remain. For example, are the annual data published in corporate reports used by investors to make decisions? Do quarterly reports add useful information? Most corporations publish comparative data that date back many years. Do stockholders use these past data? This paper seeks to answer some of these questions by determining, empirically, which published data are used by investors, as reflected by changes in the market price of common stocks. To provide a meaningful test, the relationship between common stock prices, published accounting information and other factors is specified first. Then models are developed that describe how investors may use, published accounting data. Finally the model is tested with relevant data, and conclusions are drawn.